The effect of pre-emptive analgesia on the level of postoperative pain in women undergoing surgery for breast neoplasm - Węgorowski, Paweł; Stanisławek, Andrzej; Domżał-Drzewicka, Renata; Sysiak, Justyna; Rząca, Marcin; Milanowska, Joanna; Janiszewska, Mariola; Dziubińska, Anna (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study : Dynamic development of research on pain has resulted in the formulation of the concept of pre-emptive analgesia, which involves administration of analgesics before the first pain-producing stimulus appears. It is meant to prevent increased sensitivity to pain in the postoperative period. The aim of this study was to assess the possibilities of modifying the intensity of postoperative pain evaluated with the visual analogue scale (VAS) in patients after surgical treatment for breast neoplasm offered by pre-emptive analgesia. Material and methods : The intensity of postoperative pain was measured immediately after the surgery as well as 6, 12, 18, and 24 hours later in 100 women who had undergone surgery for breast tumour. The correlation between experienced pain and the type of analgesic administered pre-emptively, including metamizole, tramadol, ketoprofen, and placebo was examined. The effect of other correlates such as the extensiveness of surgery, systolic and diastolic blood pressure, and heart rate on the level of experienced pain as well as the usefulness of physiological parameters for its assessment were also analysed. Results : The conducted study demonstrated the effectiveness of tramadol (p = 0.004) and ketoprofen (p = 0.039) administered half an hour before the beginning of surgery, but there was no similar effect in the case of metamizole (p = 1.0). A positive correlation was observed between the level of experienced pain and blood pressure values (p < 0.001). Heart rate does not seem to be significantly linked with the intensity of experienced pain (p = 0.157).